FLEXURAL BEHAVIOUR OF OIL PALM SHELL CONCRETE IN FULLY PRECAST AND SEMI-PRECAST CONCRETE SLABS - Kurian, V.J.; Doh, S.I.; Ideris, Z.; Narayanan, S.P; Gungat, L. (3rd IMS International Conference on Application of Traditional and High Performance Materials in Harsh Environments, 2008)
Six precast and six semi-precast slabs with different toppings were cast and tested for determining the flexural behaviour of concrete made using OPS (oil palm shell) as coarse aggregate. The vertical cracks in the semi-precast slabs propagated almost to the top surface of the slab without any break or discontinuity at the interface, confirming a good composite action in the slab. The investigations revealed that the type of topping did not affect the strength of the slab significantly. While OPS concrete by itself failed the deflection criterion when tested as a fully precast slab, it satisfied the requirements when used as a topping for the semi-precast slab.